Neuropixels reveal laminar microcircuit organization in monkey V1 in vivo - Nicole Carr; Shude Zhu; Xiaomo Chen; Eric Kenji Lee; Alec Perliss; Tirin Moore; Chandramouli Chandrasekaran (Proceedings of the National Academy of Sciences, 2026)
The relationship between different cell populations in monkey primary visual cortex and their role in visual function is not fully resolved. We combined high-density Neuropixels recordings across layers of macaque V1, and a state-of-the-art nonlinear dimensionality reduction approach on waveform shape to delineate nine putative cell classes: 4 narrow-spiking (NS), 4 broad-spiking (BS), and 1 triphasic (TP). Then, we performed targeted analyses of laminar organization, spike amplitude, multichannel spatial features, functional properties, and network connectivity of these cell classes. These analyses have uncovered four fundamental aspects of V1 laminar microcircuitry never fully demonstrated before in vivo. First, NS neurons were most concentrated in layer 4 and outnumbered parvalbumin positive neurons, consistent with findings on potassium channel expression in excitatory neurons in V1. Second, a large-amplitude NS cell class in layer 4b was strongly direction selective, with multichannel waveforms suggestive of a stellate morphology, a likely functional correlate of anatomical descriptions of neurons projecting from V1 to MT. Third, another NS cell class in layer 4b showed robust bursting activity and strong orientation selectivity. Finally, cross-correlation analysis revealed distinct feedforward interactions between cell classes in layer 4 and layer 5/6 and those in layer 2/3. These results demonstrate how high-resolution electrophysiology can reveal links between laminar organization and in vivo function of neurons. Our findings offer key insights for biologically realistic microcircuit models of primate V1 and may generalize to other regions.